Clinical and Biologic Significance of MYC Genetic Mutations in De Novo Diffuse Large B-cell Lymphoma - Xu-Monette, Zijun Y.; Deng, Qipan; Manyam, Ganiraju C.; Tzankov, Alexander; Li, Ling; Xia, Yi; Wang, Xiao-xiao; Zou, Dehui; Visco, Carlo; Dybkær, Karen; Li, Jun; Zhang, Li; et al. (Clinical cancer research, 2016)
Purpose: MYC is a critical driver oncogene in many cancers, and its deregulation in the forms of translocation and overexpression has been implicated in lymphomagenesis and progression of diffuse large B-cell lymphoma (DLBCL). The MYC mutational profile and its roles in DLBCL are unknown. This study aims to determine the spectrum of MYC mutations in a large group of patients with DLBCL, and to evaluate the clinical significance of MYC mutations in patients with DLBCL treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) immunochemotherapy. Experimental Design: We identified MYC mutations in 750 patients with DLBCL using Sanger sequencing and evaluated the prognostic significance in 602 R-CHOP–treated patients. Results: The frequency of MYC mutations was 33.3% at the DNA level (mutations in either the coding sequence or the untranslated regions) and 16.1% at the protein level (nonsynonymous mutations). Most of the nonsynonymous mutations correlated with better survival outcomes; in contrast, T58 and F138 mutations (which were associated with MYC rearrangements), as well as several mutations occurred at the 3′ untranslated region, correlated with significantly worse survival outcomes. However, these mutations occurred infrequently (only in approximately 2% of DLBCL). A germline SNP encoding the Myc-N11S variant (observed in 6.5% of the study cohort) was associated with significantly better patient survival, and resulted in reduced tumorigenecity in mouse xenografts. Conclusions: Various types of MYC gene mutations are present in DLBCL and show different impact on Myc function and clinical outcomes. Unlike MYC gene translocations and overexpression, most MYC gene mutations may not have a role in driving lymphomagenesis. Clin Cancer Res; 22(14); 3593–605. ©2016 AACR.